Identification and Characterization of Terpenoid Compounds Isolated from Tadalinu Stem bark of Grewia Eriocarpa Juss Extracts - Alethia E. Siahainenia; Febri O. Nitbani; Theo da Cunha (Journal of Applied Chemical Science, 2012)
The study of isolation and characterization of terpenoids in methanol extract from the stem bark of Grewia eriocarpa Juss has been conducted. The aims of the research were to know the kind of secondary metabolites, to isolate and characterize terpenoids contained in methanol extract from the stem bark of Grewia eriocarpa Juss. Maceration from 1500 gram of the stem bark powder used methanol as solvent gave 275 gram extract and there was further partitioned with petroleum ether, chloroform and water. The results of phytochemical test showed that the sample was positive for saponin, terpenoid, flavonoid and tannin. Methanol-water extract was separated with column chromathography by n-hexane:etyl acetat (1:3) as eluent and gave 6 groups of fraction. FT-IR analysis results for C fraction indicated several functional group namely OH, C=O, COOH, C-H aromatic, C=C, N-H . Based on the data of mass spectra could be estimated that the 15, 18, 20 and 27 peaks were sesquiterpenoid and the 43 peak was dyterpenoid.